Strategi Pengelolaan Pasar Tradisional Tanah Lot Dalam Upaya Meningkatkan Pendapatan Asli Desa ( PADes) Desa Adat Pekraman Beraban, Tabanan - Suari, Niti Pradnya; Sastra Wijaya, Komang Adi; Prabawati, Putu Anik (CITIZEN CHARTER, 2021)
Tanah Lot Traditional Market is the first traditional market has a modern concept in Tabanan Regency. Regarding the income of the Tanah Lot Traditional Market, it has not been able to reach the target that has been set so that it affects its contribution to the original income of the Beraban Traditional Village. The purpose of this research is to perfect or create new strategies related to the management of the Tanah Lot Traditional Market. The research method used is descriptive qualitative. The analysis used is an indicator of strategic management according to Wheelen and Hunger, namely environmental analysis, strategy formulation, strategy implementation, evaluation and control. The results of this study indicate that there are still several obstacles related to strategies that have not been maximal, program implementation has not been optimal, human resources are still low, policies implemented are not based on clear regulations. Keywoards : Traditional Market, Strategy Management, SWOT Analysis